Penguatan Moderasi Beragama melalui Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Agustina, Nelly; Zaini, Raudho; Hotimah, Fatimatu; Gajah, Nina Badriah (Ahdāf: Jurnal Pendidikan Agama Islam, 2025)
Radicalism, hedonism, and secularism have emerged as major challenges for education, particularly at the elementary school level, which plays a crucial role in shaping children’s character and worldview from an early age. This study aims to analyze the strategies implemented by elementary schools in instilling the values of religious moderation amid globalization and the digital era. The research employed a qualitative approach with a library research design, drawing on primary and secondary sources such as government documents, academic studies, and international reports. Data was analyzed through the stages of reduction, presentation, and conclusion drawing. The findings reveal that elementary schools play a strategic role in promoting inclusive religious education, empowering students, utilizing digital technology, and fostering community collaboration to strengthen religious moderation. Teachers serve as key agents of change through creative, dialogical, and culturally rooted learning, while government policies and parental involvement serve as essential supports. In conclusion, elementary schools can serve as the frontline institutions in building a young generation that is tolerant, critical, and moderate in character.